1983
DOI: 10.1161/01.hyp.5.4.535
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous opioids and baroreflex control in humans.

Abstract: SUMMARY We describe two studies designed to elucidate the role of endogenous opioids in blood pressure control in humans. In the first study, nine normal subjects received infusions of DAMME (a metenkephalin analog), naloxone, or saline, and blood pressure, heart rate, and plasma norepinephrine concentration were determined supine and following 5 minutes of 70° head-up tilt at intervals for 6 hours. Blood pressure following tilt was significantly decreased by DAMME but not influenced by naloxone, the effect be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

1984
1984
1992
1992

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 24 publications
(17 reference statements)
0
11
1
Order By: Relevance
“…Twenty-one subjects (19 men and two women aged 24+1 [mean±SEM] years) were studied in three treatment groups: 0.15 mg/kg naloxone (n=14, subjects 1-14), 0.075 mg/kg naloxone (n=13, subjects 9-21), and placebo (n=11, subjects [4][5][6][7][8][9][10][11][12][13][14]. Thus, six subjects (subjects 9-14) were studied with both doses of naloxone, and all but three subjects in the higher dose naloxone group were also studied after placebo.…”
Section: Subjects and Methods Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-one subjects (19 men and two women aged 24+1 [mean±SEM] years) were studied in three treatment groups: 0.15 mg/kg naloxone (n=14, subjects 1-14), 0.075 mg/kg naloxone (n=13, subjects 9-21), and placebo (n=11, subjects [4][5][6][7][8][9][10][11][12][13][14]. Thus, six subjects (subjects 9-14) were studied with both doses of naloxone, and all but three subjects in the higher dose naloxone group were also studied after placebo.…”
Section: Subjects and Methods Subjectsmentioning
confidence: 99%
“…The hemodynamic and MSNA responses of subjects during application of incremental LBNP (0, -5, -10, and -15 mm Hg) before and after administration of 0.15 mg/kg naloxone (subjects [1][2][3][4][5][6][7][8][9][10][11][12][13][14] and 0.075 mg/kg naloxone (subjects 9-21) are summarized in Tables 1 and 2 and Figures 1 and 2.…”
Section: Effects Ofnaloxone On Responses To Cardiopulmonarymentioning
confidence: 99%
“…The plasma noradrenaline concentration measured at the time of the fall in blood pressure produced by captopril was not significantly different either from the concentrations measured before captopril was given or from the corresponding values on the placebo day (Table 5). There is now considerable evidence to suggest that endogenous opioids modulate blood pressure control at the level of the brain stem by reducing baroreflex sensitivity (Rubin et al, 1981(Rubin et al, , 1983Petty & Reid, 1982). The absence of compensatory tachycardia in response to a fall in blood pressure produced by captopril is consistent with decreased baroreflex activity.…”
Section: Introductionmentioning
confidence: 93%
“…Opioid receptor agonists have been shown to lower blood pressure without producing a compensatory tachycardia both in animals and man (Petty & Reid, 1982;Rubin et al, 1983). Captopril inhibits carboxypeptidase, one of the enzymes responsible for the inactivation of enkephalins in vitro (Arregiu et al, 1979) and, more specifically, has also been shown to reduce the metabolism and increase the analgesic potency of metenkephalin (Stine et al, 1979 (Rubin et al, 1981) and also significantly increases baroreflex sensitivity during sodium nitroprusside infusion at this same time (Rubin et al, 1983). Since captopril has its maximum effect on blood pressure 1.5 h following administration, we concentrated data collection immediately before and 1.5 h following administration of captopril or placebo.…”
Section: Introductionmentioning
confidence: 99%
“…However, other investigators have shown that naloxone hydrochloride reduces baroreflex sensitivity in pentobarbital-anesthetized normal dogs,20 whereas it increases baroreflex sensitivity in normal cats2' and humans. 22 The reasons for the discrepant results are not known but may be related, at least in part, to the use of anesthetics, differences in animal species, or relative basal levels of endogenous opioids among the studies.…”
Section: D'iscussionmentioning
confidence: 99%